2010
DOI: 10.1016/j.breast.2010.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Differences in prognostic factors and patterns of failure between invasive micropapillary carcinoma and invasive ductal carcinoma of the breast: Matched case–control study

Abstract: Our study showed that IMPC is associated with LVI, ECE, high nuclear grade, and a greater degree of loco-regional recurrence, especially in the axilla and supraclavicular areas. Therefore, axillary and supraclavicular radiation therapy should be considered in IMPC patients with axillary node metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 23 publications
6
52
2
5
Order By: Relevance
“…15 Chen et al 16 concluded, from a large-scale, retrospective study of 636 IMPC cases and 297 735 cases of invasive breast cancer, that despite the higher propensity for LNM, IMPC had a 5-year disease-free survival and a 5-year overall survival comparable to IDC-NOS. Excitingly, the 5-year overall survival of patients with IMPC has recently improved remarkably (82.9%-89.8%), 7,14,16,17 which is at least partially due to the increasing awareness of the entity that results in timely diagnoses and appropriate clinical managements.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 3 more Smart Citations
“…15 Chen et al 16 concluded, from a large-scale, retrospective study of 636 IMPC cases and 297 735 cases of invasive breast cancer, that despite the higher propensity for LNM, IMPC had a 5-year disease-free survival and a 5-year overall survival comparable to IDC-NOS. Excitingly, the 5-year overall survival of patients with IMPC has recently improved remarkably (82.9%-89.8%), 7,14,16,17 which is at least partially due to the increasing awareness of the entity that results in timely diagnoses and appropriate clinical managements.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…7,[14][15][16][17]23,24,[37][38][39][40][41][42][43] One study of 624 patients with IMPC revealed a poor prognosis in the patients who had a tumor lacking in estrogen receptor expression. 7 The status of the HER2/neu protein expression or gene amplification in IMPC is not consistent in literature.…”
Section: Immunophenotypementioning
confidence: 99%
See 2 more Smart Citations
“…There are histological subtypes with excellent prognosis: tubular carcinoma, cribriform carcinoma, adenoid-cystic carcinoma, pure mucinous carcinoma [16], as well as subtypes associated with a worse prognosis, frequently diagnosed in a metastatic stage: micropapillary carcinoma, inflammatory carcinoma, NST carcinoma, lobular carcinoma [16,29,30]. Our study revealed that, when present in association with heterogeneous primary tumours, axillary lymph node metastases may present heterogeneous histological types (in 33.33% of cases).…”
Section: Discussionmentioning
confidence: 99%